A simulation-based feasibility assessment of malic acid production from molasses using Rhizopus arrhizus - Heriyanti; Marito, Olivia Yolanda; Huwaida, Ariqah Iffah; Ramadhan, Varrel Ariasatya; Harijanto, Fransiskus Xaverius Ray Setiadharma; Gozan, Misri; Harmami, Sri Budi (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Malic acid is a valuable organic acid widely used in food, pharmaceutical, and chemical industries. It can be sustainably produced from underutilized molasses, often classified as waste. This study evaluated the feasibility of malic acid production from molasses, using Rhizopus arrhizus. A SuperPro Designer simulation integrated process design, economic analysis, and sensitivity evaluation and the results demonstrated economic viability with a Net Present Value (NPV) of 2,140,000 (7% discount rate), an Internal Rate of Return (IRR) of 15.81%, a Return on Investment (ROI) of 22.70, and a payback period (PP) of 4.40 years for an annual production capacity of 2,830 MT. Sensitivity analysis highlighted the selling price of malic acid as the most important economic factor. This feasibility study provides a novel approach to integrate molasses-based fermentation with simulation tools, offering actionable insights for industrial-scale implementation by quantifying key economic drivers.